Al-‘Unfu fî al-Tarbiyah min Mandzûr al-Tashrî’ al-Indûnîsî wa al-Sharî’ah al-Islâmiyah - Mohammad Kosim; Faqihul Muqoddam; Faidol Mubarok (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
Violence on children has become a big unsolvable problem in Indonesian education. In fact, the government has ratified some Laws to protect them from any form of violence. Likely, Islam as the mostly followed religion in the country does the same through its mission called rahmatan li al-alamin or blessing for all. This research relies on a question on how far the Indonesian rules and Islamic law concern on this issue by protecting children from any violence. Using qualitative method in the law research and documentary analysis, it is found that the Indonesian Laws have been sufficient for that purpose as they prohibit all forms of violence against students. Along with it, the perpetrators deserve for punishment due to the mistakes level while the victims deserve for recovery and trauma healing to grow their optimism. In line with that, Islamic law also prohibits any violence because it breaks the purpose of shariah, namely enforcing the goodness (maslahah) and avoiding the harm (mudarat). However, Islamic law still tolerates hitting a child for the sake of education and their goodness as long it is performed softly and becoming the very last option. Both laws, therefore, strengthen each other to protect children from any form of violence mainly at the education sphere. لا يزال العنف نحو الأطفال في عالم التربية مشكلة كبيرة لم يتم حلها، وخاصة في إندونيسيا. في الواقع، وضعت الحكومة عددا من القوانين واللوائح لحماية الأطفال من العنف. وبالمثل، فإن الإسلام – وهو دين غالبية سكان إندونيسيا - موجود ليكون رحمة للعالمين. والسؤال الذي نركز عليه في هذا البحث هو، كيف تحمي القوانين واللوائح الحالية الطلاب من أعمال العنف، وكيف تولي الشريعة الإسلامية اهتماما للحد من العنف على الأطفال؟ ومن خلال المنهج النوعي مع البحوث القانونية وتحليل الوثائق، تبين أن القوانين واللوائح الموجودة كافية لحماية الأطفال من العنف. فالأنظمة القائمة، تمنع جميع أشكال العنف ضد الطلاب، حيث يجب معاقبة الجناة وفقا لدرجة الخطأ والذنب، ويجب تقديم المساعدة للضحية للقضاء على الصدمة وتعزيز التفاؤل، ويجب التعاون من جميع الأطراف التصدي للعنف معا. من جهة أخرى، فإن الشريعة الإسلامية تمنع وتحظر العنف ضد الأطفال لأنه يتعارض مع الغرض من الشريعة الإسلامية، وهو تحقيق الصلاح ورفع الضرر. ومع ذلك، فإن الشريعة الإسلامية تنص على السماح باستخدام العنف للأغراض التربوية من أجل مصلحة الطفل، ولكن يجب أن يتم ذلك بحذر بعناية وكملاذ أخير بعد استخدام جميع الأساليب الأخرى. إن القوانين واللوائح في إندونيسيا والشريعة الإسلامية تعزز بعضها البعض بشكل أساسي لحماية الأطفال من العنف، وخاصة في مجال التربية.